P066 A randomised, double-blind, placebo-controlled, single-dose, crossover, pilot study investigating the effects of cannabinol (CBN) 30 mg and 300 mg on sleep architecture and next-day function in insomnia disorder. (9th November 2022) - Lavender, I; Suraev, A; McCartney, D; Irwin, C; Kevin, R; D'Rozario, A; Gordon, C; Marshall, N; Saini, B; McGregor, I; Grunstein, R; Yee, B; et al.
Abstract: Introduction: There is a clear need for novel interventions for insomnia disorder. Growing evidence suggests a role of the endogenous cannabinoid system in regulating circadian sleep-wake cycles, highlighting a potential avenue for novel therapeutics. Cannabinol (CBN), a trace cannabinoid formed through oxidation of delta-9-tetrahydrocannbinol (THC), is hypothesised to impact sleep. Despite anecdotal and preclinical evidence, the effects of CBN isolate on sleep have never examined through well-designed clinical trial procedures. Methods: This randomised, double-blind, placebo-controlled, three-arm, crossover, single-site, pilot study will investigate the acute effects of oral dose CBN at 30 and 300 mg in twenty patients with clinician-diagnosed insomnia disorder (and Insomnia Severity Index [ISI] Score ≥15). Across three treatment sessions, each separated by two-weeks washout, participants will receive two doses of CBN and matched placebo, at random. Participants will undergo overnight sleep assessment using in-laboratory polysomnography and next-day neurobehavioral function tests. The primary outcomes are CBN (30 and 300 mg) effects on sleep continuity (wake after sleep onset minutes), compared to placebo, measured using polysomnography. Secondary outcomes include changes to sleep micro-architecture, traditional sleep staging, and absolute spectral power during non-rapid eye movement sleep. Various other subjective and objective safety measures will be obtained. Discussion: This study will provide novel preliminary data on the effects of CBN on sleep and next-day function in adults living with insomnia disorder which will inform the design of larger clinical trials.